The effects of different combinations of eugenol and acetic acid on quality changes of marinated rainbow trout (Oncorhynchus mykiss, W. 1792) fillets - Patır, Bahri; Can, Özlem Pelin; Emir Çoban, Özlem; Özpolat, Emine (My University, 2014)
In this study, fillets of trout marinated with different concentrations of acetic acid (2% and 4%) and eugenol (0.1% v/w and 0.5% v/w) were preserved at 4 ºC. The samples were analyzed in terms of sensory, microbiological and chemical quality. During the preservation, the total mesophilic anaerobe and Lactobacillus showed significant changes (p<0.05). Eugenol showed no significant effect on the salt and pH (p>0.05), whereas thiobarbituric acid (TBA) showed significant changes (p<0.05) in both groups and the days of preservation. In sensory analysis, flavor and general acceptability significant differences between the groups (p<0.05) during the preservation time were shown. In conclusion, marinades protected their consumed properties for at least 70 days and eugenol had favorable effects on some microbiological and chemical values. The marinades prepared with 0.1 % of eugenol were gained more acclaim in term of sensory.

Bu çalışmada, farklı konsantrasyonlarda asetik asit (%2 ve %4) ve eugenol (%0.1 v/w ve %0.5 v/w) ile marine edilen alabalık filetoları 4 ºC de muhafaza edilmiştir. Örnekler, duyusal, mikrobiyolojik ve kimyasal kalite yönünden analiz edilmiştir. Muhafaza süresince, mezofilik ve Laktik asit bakterileri önemli derecede değişim göstermiştir (p<0.05). Eugenol muhafaza süresince her iki gruptada, pH ve tuz üzerinde önemli bir etki göstermezken (p>0.05), tiyobarbitürik asit (TBA) önemli derecede değişimler göstermiştir (p<0.05). Duyusal analizde, lezzet ve genel kabul edilebilirlik muhafaza süresince gruplar arasında önemli farklılıklar göstermiştir. Sonuç olarak, marinatlar 70 gün süresince tüketilebilirlik özelliklerini korumuş ve eugenolün bazı mikrobiyolojik ve kimyasal değerler üzerine olumlu etkileri olmuştur. %0.1 eugenolle hazırlanan marinatlar duyusal bakımdan daha fazla beğeni kazanmıştır.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Eugenol; Marinade; Oncorhynchus mykiss; Acetic acit; Vacuum package; marinat; Alabalık; Asetik asit; Vakum paket